PENGARUH LOKASI, PERSEPSI HARGA, DAN PROMOSI TERHADAP KEPUTUSAN PEMBELIAN DI RESTORAN CLOVIA HOTEL MERCURE JAKARTA SABANG - Novan Andriyansyah; Rully Arifiansyah (Panorama Nusantara, 2021)
The purpose of this study was to determine and analyze the effect of location, price perception, and promotion on purchase decisions at Clovia Hotel Mercure Jakarta Sabang restaurant. The population in this study was respondents to Clovia Hotel Mercure Jakarta Sabang restaurant products with respondents of 100 respondents. The study used the accidental sampling method with the method of a multiple regression analysis. The data analysis method used in this research is multiple linear regression analysis. The results showed that the location had a significant effect on the increase in purchasing decisions, price perception had a significant effect on the increase in purchasing decisions, and promotions had a significant effect on the improvement of decisions. The F test showed that the Location, Price Perception, and Promotion jointly influenced the purchase decision at Clovia Hotel Mercure Jakarta Sabang restaurant.